Limited Face-To-Face Learning Models in the New Normal Era in UIN Sunan Gunung Djati Bandung - Tedi Priatna; Aan Hasanah; Dindin Jamaluddin; Hariman Surya Siregar; Mumu Abdurrahman (UIN Sunan Gunung Djati, 2022)
This study aims to describe the results of limited face-to-face learning in UIN Sunan Gunung Djati Bandung. This study is conducted in the Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung during the trial phase of limited face-to-face learning from October to December 2021. The data are collected from documentation and questionnaires given to students as the subject of this study. The results showed that limited face-to-face learning is conducted systematically and following the protocols during the New Normal era. This face-to-face learning is attended by 3rd-semester students from all majors. The university has planned and prepared every aspect to support the process of face-to-face learning. The process of teaching is done well and the evaluation on the effect of limited face-to-face on the quality of acquired knowledge showed a maximum score. The main obstacle during the limited face-to-face learning comes from technical aspects such as the provision of facilities and resources for conducting limited face-to-face learning. The results of this study are hoped to be used as consideration for policymakers in conducting limited face-to-face learning during the COVID-19 pandemic.